Navigation signal processing for GNSS software receivers - Pany, Thomas (Norwood, MA : Artech House, 2010)
'The advancement of software radio technology has provided an opportunity for the design of performance-enhanced GNSS receivers that are more flexible and easier to develop than their FPGA or ASIC based counterparts. Filling a gap in the current literature on the subject, this highly practical resource offers you an in-depth understanding of navigation signal detection and estimation algorithms and their implementation in a software radio. This unique book focuses on high precision applications for GNSS signals and an innovative RTK receiver concept based on difference correlators.''You learn how to develop navigation receivers for top performance using basic algorithms, like correlation and tracking, which can be understood on an intuitive level. Additionally, the book provides you with a theoretical framework for signal estimation and detection that gives you the knowledge you need to make performance assessments without building a receiver. The theoretical treatment also gives you hints for choosing optimal algorithms for your projects in the field.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Artificial satellites in navigation; Global positioning system